The Microbiology of head and neck space infections at the Maxillofacial Clinic at Livingstone Hospital - Singh, Nerisha; Ngwenya, Sizakele; Molepo, Julitha (South African Dental Journal, 2020)
INTRODUCTION: Head and neck space infections remain one of the most commonly encountered conditions at Maxillofacial clinics countrywide. Patients admitted with these infections tend to have prolonged hospital stays and often require intensive care support. This places financial and logistic constraints on our health care system. There are also growing concerns, worldwide, regarding antibiotic resistance AIMS AND OBJECTIVES: To determine the microbial spectrum of head and neck space infections in patients admitted to the Maxillo-Facial clinic at Livingstone Hospital in the Eastern Cape over a period of 5 years. METHODS: Demographic, clinical and laboratory data was retrieved from the medical records of 140 patients presenting with head and neck space infections RESULTS: Most patients were males aged 21-40 years. The most common cause of head and neck infections was non-odontogenic. The submandibular space was the most commonly implicated. Gram positive facultative anaerobes were most commonly identified. Bacteroides species and Staphylococcus aureus displayed sensitivity to clindamycin and amoxicillin with clavu-lanic acid. Viridans streptococci were sensitive to both penicillin and clindamycin CONCLUSION: Bacteroides species were the most commonly isolated bacteria, followed by Viridans streptococci and Staphy-lococcus aureus.